2012
DOI: 10.1111/j.1556-4029.2012.02215.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Volatile Organic Compounds from Different Biological Specimens for Profiling Potential*

Abstract: : Previous work has demonstrated the ability to differentiate individuals based on the analysis of human scent hand odor chemicals. In this paper, a range of forensic biological specimens are shown to also have the ability to differentiate individuals based upon the volatile organic compounds (VOCs) present. Human VOC profiles from hand odor, oral fluid, breath, blood, and urine of 31 individuals were analyzed by solid‐phase microextraction–gas chromatography–mass spectrometry (SPME‐GC‐MS) and combined methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 51 publications
2
51
0
Order By: Relevance
“…CAP of the GC-MS-SPME metabolic profiles allowed the identification of VOCs, which changed in the saliva of T-CD children. Many of the VOCs described in this study corresponded to those previously reported for the saliva of healthy individuals (37,74). These compounds may have various origins, as there are many possible routes of entry into the salivary flow, including environmental exposure through inhalation of air and/or water vapor through the lungs, ingestion through the mouth, food intake, and transdermal absorption through the skin.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…CAP of the GC-MS-SPME metabolic profiles allowed the identification of VOCs, which changed in the saliva of T-CD children. Many of the VOCs described in this study corresponded to those previously reported for the saliva of healthy individuals (37,74). These compounds may have various origins, as there are many possible routes of entry into the salivary flow, including environmental exposure through inhalation of air and/or water vapor through the lungs, ingestion through the mouth, food intake, and transdermal absorption through the skin.…”
Section: Discussionsupporting
confidence: 78%
“…These compounds may have various origins, as there are many possible routes of entry into the salivary flow, including environmental exposure through inhalation of air and/or water vapor through the lungs, ingestion through the mouth, food intake, and transdermal absorption through the skin. Moreover, microbial metabolic activities at the level of the oral cavity may also affect the synthesis of VOCs (37,74). First, this study showed some correlations between the microbiome and metabolome of children with CD.…”
Section: Discussionmentioning
confidence: 61%
“…RT, retention time; RI, retention index; N, peak number. who processed headspace collection of skin volatiles, found no or very few carboxylic acids in the skin volatiles of axillae (Mebazaa et al, 2011), hands (Zhang et al, 2005;Kusano et al, 2013) or whole body (Logan et al, 2008). Two studies (Ara et al, 2006;Caroprese et al, 2009) reported nine short-chain fatty acids in solvent extracts of foot sweat and in the interdigital area of the foot, respectively.…”
Section: Results and Discussion Chemical Composition Of Foot Volatilesmentioning
confidence: 99%
“…Helium was used as the carrier gas at 1 mL/min. Using the Varian MS Workstation Software, Version 6.6 (Service Pack 1), all compounds detected were verified and quantitated using an external calibration curve with standards that were purchased from Sigma Aldrich (St. Louis, MO) and recognized as human scent compounds [3,[13][14][15][16][17][18][19]37,40,43,44]. They included: octane; furfural; 2-furanmethanol; nonane; heptanal; 6-methyl-5-hepten-2-one; octanal; benzyl alcohol; (E)-2-octenal; 1-octanol; undecane; octanoic acid methyl ester; 1-nonanol; 2-decanone; dodecane; hexanedioic acid dimethyl ester; tridecane; undecanal; tetradecane; (E)-6,10-dimethyl-5,9-undecadien-2-one (geranyl acetone); pentadecane; and heptadecane.…”
Section: Human Scent Analysis Using Hs-spme/gc-msmentioning
confidence: 99%
“…These skin cells contain volatile organic compounds (VOCs) associated with human scent that consists of various chemical functional groups, such as carboxylic acids, alcohols, aldehydes, aliphatics/aromatics, esters, halides, heterocyclics, ketones, and nitrogen-and sulfur-containing compounds [2,3,[13][14][15][16][17][18][19]. Epithelial skin cells also contain nuclear and mitochondrial deoxyribonucleic acid (nDNA; mtDNA) that can be used to obtain an individual's DNA profile or provide maternal relatedness information.…”
mentioning
confidence: 99%